Penyuluhan Pembuatan Dan Aplikasi Pupuk Organik Pada Tanaman Kopi Di Desa Maholo Kecamatan Lore Timur Kabupaten Poso Sulawesi Tengah - Muslimin; I Nengah Korja; Annadira; Ridwan (Universitas Merdeka Surabaya, 2022)
Maholo Village is one of the villages in East Lore District, Poso Regency, located at an altitude of 1000-1700 meters above sea level. This village is suitable for coffee plantation development activities. However, the development of coffee plants is hampered due to low soil fertility. One way to overcome this problem is by adding organic matter. The addition of organic matter to the soil is known to contribute nutrients that can increase soil fertility, improve the chemical, physical and biological properties of the soil. The lack of public knowledge about this is the goal of conducting counseling activities regarding the benefits of organic materials and their processing technology. The results achieved from this activity are that community service gains knowledge and understanding of the function of organic matter on soil fertility and the community is able to carry out the manufacture and application of organic fertilizers, both independently and in groups.